192k views
3 votes
4.2y+0.8=6.2y–(1.1y+0.8)+1.2

User Black Star
by
7.5k points

2 Answers

5 votes

4.2y + 0.8 = 6.2y - (1.1y + 0.8) + 1.2

Multiply/distribute the - into (1.1y + 0.8)

4.2y + 0.8 = 6.2y - 1.1y - 0.8 + 1.2

Combine like terms

4.2y + 0.8 = 5.1y + 0.4

Subtract 4.2y on both sides

0.8 = 0.9y + 0.4

Subtract 0.4 on both sides

0.4 = 0.9y

Divide 0.9 on both sides



(0.4)/(0.9) = y

User Shahin Dohan
by
7.4k points
3 votes
Y=4/9...(tell me if you need steps)
User Keo Strife
by
8.2k points